2020
DOI: 10.1155/2020/4631290
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of B-Cell-Produced Antibodies in Vitreous Humor of Type 2 Diabetic Patients with Diabetic Retinopathy

Abstract: Aim. To analyze the levels of B-cell-produced antibodies in the vitreous humor of patients with or without diabetic retinopathy (DR) both qualitatively and quantitatively. Methods. A total of 52 type 2 diabetes mellitus (T2DM) with DR patients and 52 control subjects without diabetes mellitus or inflammatory diseases were included in this prospective study. The levels of immunoglobulin (Ig)A, IgM, and IgG subtypes were measured using a magnetic colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These results suggested that kidney damage tended to be more severe in patients with higher levels of angiogenesis and inflammation in the eye. There are substantial evidences supporting the association between DR and diabetic nephropathy (DN) (30)(31)(32)(33)(34)(35): (1) both DR and DN are characterized by diabetic microangiopathy; (2) there are common risk factors for the occurrence and progression of DR and DN; (3) the severity of DR is correlated with the degree of kidney damage; (4) multiple pathways have been considered to be involved in the development and progression of both DR and DN. On the one hand, elevated sCr and BUN and reduced eGFR in our study reflected microvascular damage of the kidney in the PDR patients.…”
Section: Correlation Analysis Revealed the Complex Relationships Between Different Angiogenesis And Inflammation Mediatorsmentioning
confidence: 99%
“…These results suggested that kidney damage tended to be more severe in patients with higher levels of angiogenesis and inflammation in the eye. There are substantial evidences supporting the association between DR and diabetic nephropathy (DN) (30)(31)(32)(33)(34)(35): (1) both DR and DN are characterized by diabetic microangiopathy; (2) there are common risk factors for the occurrence and progression of DR and DN; (3) the severity of DR is correlated with the degree of kidney damage; (4) multiple pathways have been considered to be involved in the development and progression of both DR and DN. On the one hand, elevated sCr and BUN and reduced eGFR in our study reflected microvascular damage of the kidney in the PDR patients.…”
Section: Correlation Analysis Revealed the Complex Relationships Between Different Angiogenesis And Inflammation Mediatorsmentioning
confidence: 99%
“…Recently, it has been shown that B cell activation is involved in the pathogenesis of diabetic retinopathy ( Liu et al, 2020 ) and RPE cells can inhibit B cell activation ( Sugita et al, 2010 ). Therefore, it could be possible that subthreshold micropulse laser could also activate RPE cells to suppress B cell activation.…”
Section: Discussionmentioning
confidence: 99%